Oxygenic and anoxygenic photosynthesis in a microbial mat from an anoxic and sulfidic spring. (20th February 2017) - de Beer, Dirk; Weber, Miriam; Chennu, Arjun; Hamilton, Trinity; Lott, Christian; Macalady, Jennifer; M. Klatt, Judith
Summary: Oxygenic and anoxygenic photosynthesis were studied with microsensors in microbial mats found at 9‐10 m depth in anoxic and sulfidic water in Little Salt Spring (Florida, USA). The lake sediments were covered with a 1‐2 mm thick red mat dominated by filamentous Cyanobacteria, below which Green Sulfur Bacteria (GSB, Chlorobiaceae) were highly abundant. Within 4 mm inside the mats, the incident radiation was attenuated to undetectable levels. In situ microsensor data showed both oxygenic photosynthesis in the red surface layer and light‐induced sulfide dynamics up to 1 cm depth. Anoxygenic photosynthesis occurred during all daylight hours, with complete sulfide depletion around midday. Oxygenic photosynthesis was limited to 4 h per day, due to sulfide inhibition in the early morning and late afternoon. Laboratory measurements on retrieved samples showed that oxygenic photosynthesis was fully but reversibly inhibited by sulfide. In patches Fe(III) alleviated the inhibition of oxygenic photosynthesis by sulfide. GSB were resistant to oxygen and showed a low affinity to sulfide. Their light response showed saturation at very low intensities.